Tunable dual-wavelength ytterbium-doped fiber laser using a strain technique on microfiber Mach–Zehnder interferometer - Ahmad, Harith; Salim, M.A.M.; Azzuhri, Saaidal Razalli; Jaddoa, M.F.; Harun, Sulaiman Wadi (Optical Society of America, 2016)
In this paper, stable dual-wavelength generation using a strain technique for a ytterbium-doped fiber laser is successfully demonstrated. A microfiber-based Mach-Zehnder interferometer is inserted into the laser ring cavity and stretched using the xyz translation stage. Four sets of dual-wavelength output lasing are obtained when the strain is applied onto a microfiber. The dual-wavelength output possesses spacing between 7.12 and 11.59 nm, with displacement from 2 to 190 μm from the central wavelength. The obtained side-mode suppression ratio is ∼48 dBm, while the maximum power fluctuation and wavelength shift are less than 0.6 dB and 0.01 nm, respectively. The results demonstrate that this setup generates a stable dual-wavelength laser in the 1 μm region.